“Keseimbangan Otonomi Lokal dan Kesatuan Doktrinal: Kajian Pemerintahan Gereja Dalam Konteks Masa Kini” - Darmadi, Daud; Paruntu , Leonardo (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2024)
This study analyzes various church governance models, namely Episcopal, Presbyterian, Congregational, and Synodal, using a SWOT analysis method to examine each system's strengths, weaknesses, opportunities, and threats. Each governance model possesses structural characteristics that impact decision-making, authority distribution, and the relationship between congregants and church leaders. The results show that each system offers a unique approach to maintaining doctrinal unity and enhancing congregational participation. However, no governance model is entirely ideal; each faces challenges in balancing centralized authority with local autonomy. Therefore, this study also proposes fundamental principles, such as collaborative leadership, distributed accountability, holistic theological formation, sustainable resource management, and responsiveness to social challenges, which can be applied to optimize church governance functions in an ever-evolving social and cultural context.